Non-Linear Contact Finite Element Analysis Of Split Hopkinson Incident Bars Under Impact Load - Ng, Yie Yen (Universiti Sains Malaysia, 2021)
A high strain rate testing system is important to define whether the component’s design can resist impact loading. Therefore, Split Hopkinson Pressure Bar (SHPB) development is important for studying material behaviour at high strain rates. However, from the literature review conducted in this project, it was found that no publication gave a specific guideline to determine the design parameters of a Tensile SHPB and to characterize the stresses experienced by the SHPB’s components. The purpose of this project was to characterize the stresses of an incident bar and use the simulation result to propose a design guideline for the development of a small-scale Tensile SHPB by using Ansys Mechanical APDL. To carry out the analysis, the geometry created in the simulation followed the actual material and dimension of Tensile SHPB developed in the Mechanical Engineering laboratory. The approach for the finite element analysis was based on contact mechanics to simulate the working principle of the SHPB. An experimental setup in a related testing configuration was used as the loading parameter in the simulation. Using this loading configuration, the finite element model demonstrated that the maximum stress experienced by the incident bar under frictionless conditions was 677MPa. Subsequently, pressure and friction losses were estimated to make the simulation a sensible outcome; the stress of 403.50MPa was obtained from the calculation. Moreover, small-scale SHPB was set to fit onto a 1.8m x 1.2m regular table using the stress ratio